Literature Review on Salary Management Research in Chinese Vocational Colleges - Hongyun Liao (Journal of Advanced Research in Education, 2024)
By reviewing the literature on salary management in Chinese vocational colleges in recent years, it is found that the research topics of salary management in Chinese vocational colleges in recent years mainly focus on basic theoretical research, current situation and problems, optimization strategies, information construction, non-economic incentives, fairness and incentives, as well as the limitations of existing research. Summarized the shortcomings of current research on salary management in Chinese vocational colleges, and finally identified areas for further research in the future. This comprehensive review can provide strong theoretical support and practical guidance for the in-depth development and research of salary management in Chinese vocational colleges and promote the continuous construction of the university teaching staff to a new level.